Tax Avoidance Behavior in Manufacturing Firms - Puspita Ningrum, Sophia; Junaidi; Indra Purnama, Yunus; Sayekti, Fran (E-Jurnal Akuntansi, 2026)
Tax avoidance is a legal strategy used by companies to minimize tax burdens by taking advantage of gaps within tax regulations. This phenomenon has attracted increasing attention because it may reduce government tax revenue, particularly in manufacturing firms that often have broader opportunities for tax efficiency. This study empirically examines the effects of transfer pricing, capital intensity, and inventory intensity on tax avoidance among manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Transfer pricing refers to pricing decisions in transactions between related parties, capital intensity reflects the proportion of fixed assets to total assets, and inventory intensity measures the proportion of inventories to total assets. The study employs a quantitative approach using secondary data obtained from companies’ annual financial statements and annual reports. Samples were selected using purposive sampling based on predetermined criteria, resulting in 37 firms and a final dataset of 185 firm-year observations. Data was analyzed using multiple linear regression with SPSS version 25. The results indicate that capital intensity has a statistically significant effect on tax avoidance, whereas transfer pricing and inventory intensity are not statistically significant determinants of tax avoidance.